Socialization: Improving the Quality of Lecturers' Workload by Avoiding Predatory Journals: Pengabdian - Wiranti Kusuma Hapsari; Petrus Jhon Alfred D. D; Liani Sari; Liza Utama; Chrismesi Pagiu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service (PkM) activity aims to improve the quality of Lecturer Workload (BKD) reporting and the integrity of lecturers' scientific publications through intensive outreach on identifying and avoiding predatory journals. Improving the quality of BKD is crucial considering that scientific publications are a key component in evaluating academic performance and submitting Credit Points (AK). The PkM was implemented in the form of a one-day workshop and outreach at each of the authors' affiliated campuses. The implementation method included material delivery (interactive lectures) and hands-on practice (journal identification simulations using Beall and DOAJ/Scopus criteria). Effectiveness was measured by comparing pre-test and post-test results to assess improvements in lecturers' competency and awareness. A total of 90 lecturers from three affiliated campuses fully participated in this activity. Statistical analysis showed an average increase in knowledge scores of 35% in the post-test (p < 0.01), indicating that the outreach successfully improved lecturers' understanding of the characteristics of predatory journals (e.g., promises of rapid publication, hidden fees, and lack of a credible peer-review process). Furthermore, there was an increase in lecturers' confidence in selecting reputable journals. This outreach model has proven effective in equipping lecturers with the knowledge and practical skills needed to protect their scientific work from the threat of predatory journals. The primary contribution of this PkM is to support higher education institutions' efforts to ensure the quality of Tridharma outputs and maintain the accountability of the BKD (Regional Research Service Agency) in accordance with national standards.